PENGARUH HARGA DAN KEPERCAYAAN KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN PRODUK PADA SOCIAL E-COMMERCE TIK TOK DI KOTA BANJARMASIN - Honey Ike A’isyah; Noor Hidayati; Nurul Wahyuni; Setio Utomo (Smart Business Journal (SBJ), 2023)
This ponder points to decide and test mostly and at the same time the impact of Cost and Customer Believe on Item Buy Choices on Social E-Commerce Tik Tok in Banjarmasin City. This inquire about may be a quantitative inquire about, this investigate plan is acquainted. Examining in this think about utilized a purposive examining strategy, in arrange to get 140 respondents who were utilized as inquire about tests utilizing the Ferdinand equation with a least number of tests of 110. The information utilized was taken from a survey. Information investigation utilizing numerous direct relapse investigation. The comes about appeared that (1) the sig X1 esteem was 0.000 <0.05, so there was a fractional noteworthy impact on Cost on Item Acquiring Choices on Social E-Commerce Tik Tok in Banjarmasin City, (2) sig X2 value was 0.000 <0, 05, at that point there's a fractional noteworthy impact on Buyer Trust on Item Obtaining Choices on Social E-Commerce Tik Tok within the City of Banjarmasin, (3) the sig esteem on the synchronous test is 0.000 <0.05, at that point there's a simultaneous significant impact on Cost and Customer Believe Against Item Obtaining Choices on Social E-Commerce Tik Tok within the City of Banjarmasin.